Productivity increase in a dairy cattle company in the Arequipa region, Peru, applying lean manufacturing - Puertas Aragon, Carlos Nicolas (2024)
This article presents the result of research on the impact of lean manufacturing methods applied to the milking process of a livestock company in Arequipa. It presents the industry's context, current state, and problems. Then, it discusses the methodology and presents the pre-test status, 5S, kanban, and housekeeping implementation, as well as the post-test status. Finally, it discusses the findings and conclusions. The study shows that lean manufacturing methods are effective in the company, achieving a 12,66 % increase in productivity. Additionally, organization, process standardization, and elimination of non-value-added elements lead to a 25 % reduction in delays. Furthermore, milk loss decreased by 16,28 % due to cleanliness and the implementation of health controls. By reducing process time, energy consumption, and input usage, direct costs on income decreased by 9,34 %.